A Quality Outcome Assessment of Learning Discrete Mathematics Course The Case of University Students - Shing, Marn-Ling; Shing, Chen-Chi; Shing, Lee-Pin; Shing, Lee-Hur (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2007)
Teaching a mathematics foundation course such as Discrete Mathematics for an information technology curriculum is always a challenge. The challenge may be identifying students mathematical backgrounds early and then using different teaching techniques in the classroom. An even bigger challenge is that many topics have to be covered effectively in a short semester course. This paper provides a standard quantitative methodology for conducting an outcome assessment using Discrete Mathematics as a case study. It starts with creating an ABET accredited course outcome based on different learning levels. And then it shows how to design assessment instruments, how to determine the sample size, how to collect data and how to analyze and validate the data.